2022
DOI: 10.1038/s42003-022-03160-y
|View full text |Cite
|
Sign up to set email alerts
|

A leafhopper saliva protein mediates horizontal transmission of viral pathogens from insect vectors into rice phloem

Abstract: Numerous insects transmit viruses together with saliva to plant phloem, but the roles of saliva components remain elusive. Here, we report that calcium-binding protein (CBP), a universal insect saliva protein, is modified to benefit horizontal transmission of a devastating rice reovirus into plant phloem. CBP effectively competes with virus-induced filaments to target and traverse actin-based apical plasmalemma into saliva-stored cavities in salivary glands of leafhopper vector. Thus, the inhibition of CBP exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…CBPs are also involved in the transmission of devastating viruses into plant phloem. Viral infection may inhibit CBP expression and this event facilitates filament-mediated viral secretion first into salivary cavities and then into plant phloem which in rice causes an increased [Ca 2+ ] cyt , followed by a substantial H 2 O 2 production [ 67 ].…”
Section: Calcium Binding Proteins (Cbps)mentioning
confidence: 99%
“…CBPs are also involved in the transmission of devastating viruses into plant phloem. Viral infection may inhibit CBP expression and this event facilitates filament-mediated viral secretion first into salivary cavities and then into plant phloem which in rice causes an increased [Ca 2+ ] cyt , followed by a substantial H 2 O 2 production [ 67 ].…”
Section: Calcium Binding Proteins (Cbps)mentioning
confidence: 99%
“…A recent study on leafhoppers revealed that the expression of a saliva calcium-binding protein is inhibited by rice gall dwarf virus (RGDV), thus causing an increase of cytosolic Ca 2+ levels in rice and triggering callose deposition and H 2 O 2 production. This increases the frequency of insect probing, thereby enhancing viral horizontal transmission into the rice phloem (Wu et al, 2022). Direct saliva protein-pathogen interactions have been reported in animal pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…During plant virus transmission by piercing-sucking insects, arboviruses are inoculated into the plant phloem via the secreted insect's saliva (Arca & Ribeiro, 2018;Conway et al, 2016;Wu, Yi, Lv, Mao, & Wei, 2022). Thus, insect saliva acts as an interface for the virus-insect-host tripartite interaction and it can directly promote pathogen transmission to, and infection of, the hosts (Sun et al, 2020;Wu et al, 2022). However, despite the importance of insect salivary proteins in the tripartite interaction, there is still much to learn about how these proteins enable successful viral infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such viruses traverse the intestine, cycle through the hemocoel and accumulate in the salivary glands, before inoculation as a saliva component into new plant hosts. During their passage, they can interact with various host organs, for example the brain, the salivary glands or antenna and modify vector behavior in ways that are conducive to virus transmission [ 18 20 ]. Similar manipulations have also been described for other pathogens that replicate in their vectors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%